ESPM-EEP%202010%20Lecture%204

G see bellows 1982 juvenileadult model xt 1 f xt

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: : xt +1 = f ( xt , xt −1 ) • Two first order equations (e.g. see Bellows, 1982, juvenile/adult model): xt +1 = f ( xt , yt ) yt +1 = g ( xt , yt ) • How to turn a second order equation into two first order equations In the equation xt +1 = f ( xt , xt −1 ) , define yt = xt −1 . Then this equation can be written as xt +1 = f ( xt , yt ) yt +1 = xt 6. Mandelbrot Set and Julie Sets. (At bspace website under Lecture Notes download Mandelbrot pdf) 7. Websites: http://en.wikipedia.org/wiki/Mandelbrot_set...
View Full Document

Ask a homework question - tutors are online